PENGARUH STRATEGI GENIUS LEARNING DENGAN PENGGUNAAN POWER POINT TERHADAP PEMAHAMAN KONSEP MATEMATIS SISWA KELAS VIII MTSN DURIAN TARUNG PADANG - Oktariza, Wenny; Rismen, Sefna; Anggraini, Villia (STKIP PGRI Sumbar, 2013)
The background of this research was studentsâ mathematic understanding which was still low. The purposes of this research were: 1) is studentsâ mathematic concept understanding through Genius Learning strategy by using Power Point better than a conventional Strategy that is applied to Eight Grade Students in MTSN Durian tarung in year 2012/2013. 2) To find out studentsâ motivation before and after being treated through genius learning by using Power Point. This research is an Experimental Research with random arrangement toward the subject of this research. The research population is all Eight Grade students which consist of five classes and the sample of the research is VIII2 AS experimental class and VIII1 as control class. The instruments used in this research are 1) motivation questionnaire 2) essay posttest with test reliability 0,708. MINITAB software used in this research to get the T-value = 2,76, it means better that ttabel = 1,645. In result, the hypothesis is accepted. In conclusion, Genius Learning strategy by using Power Point is better than a conventional strategy toward studentsâ mathematic concept understanding through that is applied to Eight Grade Students in MTSN Durian Tarung and studentsâ motivation increased.